2008
DOI: 10.1016/j.chemphyslip.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biological functions of docosahexaenoic acid in the nervous system: modulation by ethanol

Abstract: Docosahexaenoic acid (DHA, 22:6n-3), an n-3 fatty acid highly concentrated in the central nervous system, is essential for proper neuronal and retinal function. While a high level of DHA is generally maintained in neuronal membranes, inadequate supply of n-3 fatty acid or ethanol exposure leads to a significant loss of DHA in neuronal cells. The roles of DHA in neuronal signaling have been emerging. In this review, biological, biochemical and molecular mechanisms supporting the essential function of DHA in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…In agreement, it was observed that depletion of n-3 PUFAs activates caspases in brains of transgenic mice models of Alzheimer's disease [183,184]. Promotion of neuronal survival was elicited by DHA also in mouse neuroblastoma Neuro 2A cells in vitro [185,186]. Consistently, the same authors found that maintaining female pregnant rats to a diet deficient in n-3 PUFAs dramatically increased apoptosis in n-3 PUFA-deficient fetal hippocampal primary cultures under trophic factor withdrawal conditions.…”
Section: N-3 Pufas and Apoptosis In Other Fields Of Human Healthsupporting
confidence: 60%
“…In agreement, it was observed that depletion of n-3 PUFAs activates caspases in brains of transgenic mice models of Alzheimer's disease [183,184]. Promotion of neuronal survival was elicited by DHA also in mouse neuroblastoma Neuro 2A cells in vitro [185,186]. Consistently, the same authors found that maintaining female pregnant rats to a diet deficient in n-3 PUFAs dramatically increased apoptosis in n-3 PUFA-deficient fetal hippocampal primary cultures under trophic factor withdrawal conditions.…”
Section: N-3 Pufas and Apoptosis In Other Fields Of Human Healthsupporting
confidence: 60%
“…Potential mechanisms by which DHA may improve outcomes include increasing cell survival [98100] and/or improving process outgrowth and synaptogenesis [22, 25, 101, 102]. Prenatal ethanol exposure also significantly alters membrane phospholipid species, particularly phosphatidylserine, in brain [49, 55, 103, 104]. More than 35% of the fatty acids in phosphatidylserine are DHA [105], thus, increasing dietary DHA may support membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In brain, DHA is highly enriched, especially in the sn-2 position of PS and PE ( 44,45 ), and such enrichment of DHA has been shown to be essential for normal brain function and development (15)(16)(17). Although critical need for PSS2 in the brain has not been demonstrated, higher expression and activity of PSS2 occur in the fetal brain during embryonic development where DHA is rapidly accumulating, compared with the adult brain ( 46 ).…”
Section: Discussionmentioning
confidence: 99%